Analisa Keputusan Konsumen Dalam Memilih Bank Umum Mandiri Dan Bank Muamalat di Kabupaten Lumajang - Hartono, Rudi; Wiranata, Roni (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2018)
The number of banking companies with a wide range of products and facilities offered raises a complexity of its own for prospective customers to specify where to save. In a complex situation like this, it would require an in-depth and systematic thinking before making a decision. Thus the need to draw up a priority level, agree that in a certain period, the choice of which one will be more important than the other options, and consideration in order to get an effective decision. Research on scientific writing is the consumers decision to Commercial Bank Mandiri and Bank Muamalat in Lumajang. Through the interview techniques descriptive analysis using data analysis by Miles and Hubermen, which this analysis is done in an interactive and takes place continuously until complete. Activities in the analysis of this data is to summarize, selecting subject matter, focusing on things that are important to look for themes and patterns (data reduction), then the data is presented in a pattern corresponding to the study (data display), and thereafter drawn a conclusion that generates a hypothesis and a description or picture of an object that previously were dim or dark becomes clear. Results of this study was obtained from interviews Customers Bank Mandiri and Bank Muamalat KCP Lumajang Lumajang. In this study the number of informants in the interview as many as 10 people. From the analysis and discussion that has been done, it can take some conclusions Turns Conventional their perceptions of the bank is more dominant and their decisions as the most Top Needs. As well as existing facilities can be met all the needs of each - each informant. Meanwhile Muamalat Islamic banks are more likely to special interests such as personal Haj Savings, Savings Home, Education and etc. Moreover, the existing facilities in the Islamic bank is incomplete and not fulfilled all by people like ATMs less extensive coverage unlike in a conventional bank very broad scope to the outlaying place. Factors Services, ATM Facility, Building, Location, Convenience and Parking are dominant and still less compared to conventional.